GeneXpert MTB/RIF Assay for the Diagnosis of Tuberculous Lymphadenitis on Concentrated Fine Needle Aspirates in High Tuberculosis Burden Settings - Tadesse, Mulualem (PLoS One, 2015)
INTRODUCTION: The diagnosis of tuberculous lymphadenitis (TBL) remains challenging. The routinely used methods (cytology and smear microscopy) have sub-optimal sensitivity. Recently, WHO recommends GeneXpert to be used as the initial diagnostic test in patients suspected of having extra-pulmonary tuberculosis (EPTB). However, this was a conditional recommendation due to very low-quality evidence available and more studies are needed. In this study we evaluated the performance of Xpert for the diagnosis of TBL on concentrated fine needle aspirates (FNA) in Southwest Ethiopia. METHODS: FNA was collected from presumptive TBL cases. Two smears were prepared from each aspirate and processed for cytology and conventional microscopy. The remaining aspirate was treated with N-acetyl-L-cysteine-NaOH and centrifuged for 15minutes at 3000g. The concentrated sediment was used for culture and Xpert test. Capilia TB-Neo test was used to differentiate M. tuberculosis complex (MTBC) from non-tuberculous mycobacteria (NTM). Composite bacteriological methods (culture and/or smear microscopy) were considered as a reference standard. RESULT: Out of 143 enrolled suspects, 64.3% (92/143) were confirmed TBL cases by the composite reference standard (CRS). Xpert detected M. tuberculosis complex (MTBC) in 60.1% (86/143) of the presumptive TBL cases. The sensitivity of Xpert compared to CRS was 87.8% [95% CI: 81.0–94.5] and specificity 91.1% [95% CI: 82.8–99.4]. The sensitivity was 27.8% for smear microscopy and 80% for cytology compared to CRS. Cytology showed the lowest specificity (57.8%). Xpert was positive in 4 out of 45 culture- and smear-negative cases. Among 47 cytomorphologically non-TBL cases, 15 were positive on Xpert. More than half of Xpert-positive cases were in the range of very low cut-off threshold values (28<Ct<38). Resistance to rifampicin was identified in 4.7% (4/86) of Xpert-positive cases. CONCLUSION: Xpert test showed a high sensitivity and specificity for the diagnosis of TBL on concentrated FNA samples. In addition, Xpert offered rapid detection of rifampicin-resistant M. tuberculosis strains from lymph node aspirates.